Research on Radio Network Intelligent Frequency Selection Technology Based on an Adaptive Genetic Algorithm - Wenjun Wang (Dianxin kexue)
In order to solve the problem of selecting frequency more and more difficultly for radio network,an intelligent frequency selection technology based on an adaptive genetic algorithm was proposed.Frequencies were selected for whole radio network from the perspective of intelligent optimization.On the basis of the standard genetic algorithm,this novel method improved genetic operators,and the preservation of the optimal individual algorithm to ensure the diversity of the population was introduced.Therefore,the arithmetic which did well in avoiding some deficiencies of the traditional frequency selection algorithm prevented local optimization and ran into overall optimization ultimately.Theoretical analysis and simulation results show that the new algorithm in solving the problem of frequency selection for large-scale network has higher efficiency and precision than the traditional algorithm,and stability is significantly enhanced.